Kebutuhan Kompetensi Dakwah Healing Dan Konseling di Dunia Kerja - Radhiya Bustan (Universitas Al Azhar Indonesia, 2011)
There is a gap between the outcomes of higher education and the demands of competence in the workplace (Observation Teichler, 1997, 1999; Yorke and Knight, 2006). It is necessary to anticipate and evaluation conducted by the universities to the needs of the working world of the competence of its graduates. For this reason, preaches study program of Healing and Counseling at University of Al Azhar Indonesia needs to put through research, whether Healing and Counseling Program will be able to achieve the vision of its mission into educational institutions that can print a preacher who can do the required counseling Islam in society and the world of work today . This study aims for Healing and Counseling Studies Program to conduct an evaluation of the competencies needed by the real world of work in society and to adapt appropriate teaching curriculum. The results showed that the competence of graduates of Healing and Counseling Program UAI was needed in the world of work and competence in the appropriate field for Healing and Counseling is generally associated with human resources (HR) or Human Resources Department, namely as a counselor, therapist, spiritual counselor / preachers, volunteers for various family problems, physical, educational, religious, Islamic law, and violence.